EVALUATION OF NUTRITIONAL STATUS AND ITS RELATIONSHIP WITH FUNCTIONAL STATUS AND FRAILTY - Reos, M. (Innov Aging, 2017)
MATERIAL AND METHOD: Cross-sectional observational study of patients over 60 years institutionalized during January and February 2016. All patients were evaluated for: nutritional status with Mini Nutritional Assessment (MNA), degree of dependence based on the Barthel scale and fragility according to Fried criteria. RESULTS: 70 patients, 41 women and 29 men were evaluated. The average age for women was 79.34 +/- 11 years and for men 70.72 +/- 8.9 years. Regarding the nutritional assessment, 21.23% did not show nutritional risk, 32.85% presented risk of malnutrition and 45.71 % were malnourished. 50% of the patients studied had full or severe dependence, the largest percentage in women (women 51% and men 41%), 28.5% showed no dependence, with a higher percentage in men. (34% men and 24% women). 70% of all cases observed were frail, being more frequent in the female population (women 78% and men 58%). Statistical significant association was found between the nutritional status and the presence of frailty (r: 0.56 p: 0.000) as well as between nutritional status and degree of functionality (r:0.49 p:0.000). CONCLUSIONS: Malnutrition showed statistical association with functionality and frailty in our patients Our results emphasized the importance of including nutritional evaluation in the global geriatric assessment to raise multidisciplinary strategies and manage more efficiently the expenses in the third level of attention.